Nanomaterials in the Future Biotextile Industry: A New Cosmovision to Obtain Smart Biotextiles - Gomez-Luna, M (Frontiers Media S.A., 2022)
For centuries, man has dominated the development of fibers and textiles to make clothing that protects them against environmental adversities, and gradually dissimilar cultural and ethnic identity traits have been created. Our garments are composed of natural elements such as animal leather, vegetable fibers, and synthetic textiles that result in ultra-resistant and durable materials. However, the textile industry has a non-sustainable character mainly because population growth will limit the use of natural resources, such as land and water, exclusively for food. At the same time, petrochemical-derived materials will gradually be replaced by more biodegradable alternatives due to their toxic accumulation in the local environment and their contribution to global climate change. The vast inventiveness of human-being is opening the possibility of replacing our clothes by mimicking, reproducing, and scaling up nature’s biosynthetic machinery through cutting-edge biotechnological approaches. Nevertheless, the new cosmovision of biotextiles must meet two requirements: 1) the appearance and performance of the clothes should be preserved to join the current textile market demand, and at the same time, 2) new functionalities should be incorporated into our clothes to embrace the impressive technological advances occurring day to day. In this regard, nanotechnological developments will be able to provide the desired properties so that the textile industry can provide bio-based materials enhanced with nanotechnology-based intelligent functionalities. This perspective article discloses nano-biotechnological approaches to address the challenge of dressing up future societies and new material consciousness. Copyright © 2022 Fuentes, Gómez, Rebolledo, Figueroa, Zamora and Naranjo-Briceño.